Does ASEAN Matter? : A View from Within - Natalegawa, Marty (Book collections on Project MUSE., 2018)
Written by the highly regarded diplomat Marty Natalegawa, former ambassador and foreign minister of Indonesia, this book offers a unique insider-perspective on the present and future relevance of ASEAN. It is about ASEAN's quest for security and prosperity in a region marked by complex dynamics of power. Namely, the interplay of relations and interests among countries -- large and small -- which provide the settings within which ASEAN must deliver on its much-cited leadership and centrality in the region. The book seeks to answer the following questions: How can ASEAN build upon its past contributions to the peace, security and prosperity of Southeast Asia, to the wider East Asia, the Asia-Pacific and the Indo-Pacific regions? More fundamentally and a sine qua non, how can ASEAN continue to ensure that peace, security and prosperity prevail in Southeast Asia? And, equally central, how can ASEAN become more relevant to the peoples of ASEAN, such that its contributions can be genuinely felt in making better the lives of its citizens?